Building a Community of Practice Among Online EdD students - Linda Lopez-George (Adult Education Research Conference, 2023)
To address feelings of isolation among online doctoral students an action research paradigm explored a virtual community of practice with computer-mediated communication tools integrated in the mixed methods study.
Keywords: virtual communities of practice; doctorate programs; social connectedness; student success